Effect of Topical Dayak Onion (Eleutherine palmifolia) Cream on Epidermal Thickness in UVB-Exposed Male Wistar Rats: An Experimental Study - Aditya Putri Setyanegari; Galih Sari Damayanti; Liza Afriliana; Vega Karlowee (Faculty of Medicine, Diponegoro University, 2025)
Background: Exposure to ultraviolet B (UVB) radiation, particularly in tropical regions like Indonesia, can cause skin damage characterized by increased epidermal thickness due to keratinocyte hyperproliferation, contributing to photoaging. Natural photoprotective agents rich in antioxidants such as Dayak onion (Eleutherine palmifolia) extract are expected to mitigate these effects. Objective: This study aims to evaluate the effect of applying Dayak onion extract cream at varying concentrations on epidermal thickness of UVB-induced male Wistar rat skin. Methods: This study was a true experimental study with a post-test only control group design. A total of 36 male Wistar rats were randomly divided into four groups: a control group (given placebo cream) and three treatment groups given Dayak onion extract cream at concentrations of 10%, 15%, and 20%. UVB exposure was carried out every two days for 30 days, along with application of the cream before and after UVB radiation. Epidermal thickness was analyzed through histopathological examination using Hematoxylin-Eosin staining and observed under 400x magnification. Results: Statistical analysis showed significant differences (p < 0,05) in epidermal thickness between the control group and the treatment groups. The mean epidermal thickness in the treatment groups was lower than that of the control group, with the greatest reduction observed in the 20% concentration group, followed by the 15% and 10% groups. There was no significant difference between the 15% and 20% concentrations. Conclusion: Application of Dayak onion extract cream is effective in reducing epidermal thickness, with a concentration of 20% providing optimal protective effects. These findings support the potential of Dayak onion as a natural photoprotective agent.Keywords: Dayak onion, Eleutherine palmifolia, epidermal thickness, photoaging, antioxidant